Long- and short-term CDK5 knockdown prevents spatial memory dysfunction and tau pathology of triple transgenic Alzheimer's mice (2014)
ABSTRACT: CDK5 is a member of the cyclin-dependent kinase family with diverse functions in both the developing and mature nervous system. The inappropriate activation of CDK5 due to the proteolytic release of the activator fragment p25 from the membrane contributes to the formation of neurofibrillary tangles and chronic neurodegeneration. At 18 months of age 3xTg-AD mice were sacrificed after 1 year (long term) or 3 weeks (short term) of CDK5 knockdown. In long-term animals CDK5 knockdown prevented insoluble Tau formation in the hippocampi and prevented spatial memory impairment. In short-term animals, CDK5 knockdown showed reduction of CDK5, reversed Tau aggregation, and improved spatial memory compared to scrambled treated old 3xTg-AD mice. Neither long-term nor shortterm CDK5 knock-down had an effect on old littermates. These findings further validate CDK5 as a target for Alzheimer’s disease both as a preventive measure and after the onset of symptoms.